-9h+15=27-2h

Simple and best practice solution for -9h+15=27-2h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9h+15=27-2h equation:


Simplifying
-9h + 15 = 27 + -2h

Reorder the terms:
15 + -9h = 27 + -2h

Solving
15 + -9h = 27 + -2h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '2h' to each side of the equation.
15 + -9h + 2h = 27 + -2h + 2h

Combine like terms: -9h + 2h = -7h
15 + -7h = 27 + -2h + 2h

Combine like terms: -2h + 2h = 0
15 + -7h = 27 + 0
15 + -7h = 27

Add '-15' to each side of the equation.
15 + -15 + -7h = 27 + -15

Combine like terms: 15 + -15 = 0
0 + -7h = 27 + -15
-7h = 27 + -15

Combine like terms: 27 + -15 = 12
-7h = 12

Divide each side by '-7'.
h = -1.714285714

Simplifying
h = -1.714285714

See similar equations:

| 76-4x=7x-21 | | 6m-7n^5/3m^3*n^3 | | 1/3×21 | | 10x+8(x-3)-8= | | -6(x-1)-7=-7x+7 | | 10.8a+9.8a-7.9=-7.6 | | (x+6)((2x-1)(x+6))=0 | | (3b-4)(6b+5)-2= | | x=4/3×3.14×7^3 | | -14a+9=11a+12 | | 4/7=2c | | 2n+b-3n=-6 | | f(x)=(x^2-3x-1)/x | | R^2-9/2r=29 | | 0=-16t^2+10t+56 | | -25+3x=0 | | 20n-19n+21=-21 | | x=4/3×3.14×7×7×7 | | 1/x^2-4=0 | | 15x-177=6x-6 | | 4x+4=3y+6 | | Log[9]5+log[9]4= | | 7.3=(2x)/(.3-x) | | X/5=x-7/7 | | 3/17x=-6 | | 15x^4+6x^2-18x^3= | | n/-1.8=2.1 | | 7x+8=9-(4x-9) | | -16x^2+1000x+3=9 | | 4x+y=225 | | -3=4w | | 3y-6=21x |

Equations solver categories